Effect of blood pressure on mortality in patients with cognitive impairment: a prospective cohort study - Shang, YanChang; Wang, ShuHui; Wei, Chao; Gao, ZhongBao; Xie, HengGe; Wang, ZhenFu (Frontiers in Cardiovascular Medicine, 2023)
Background: Cognitive impairment is a prevalent condition that substantially elevates mortality rates among the elderly. The impact of hypertension on mortality in older adults with cognitive impairment is a subject of contention. This study aims to examine the influence of hypertension on both all-cause and CVD-specific mortality in elderly individuals experiencing cognitive impairment within a prospective cohort. Methods: This study encompassed 2925 participants (weighted 53,086,905) aged 60 years or older from National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2014. Incidence of all-cause and CVD-specific mortality was ascertained through linkage with National Death Index records until December 31, 2019. Survival was performed employing the Kaplan-Meier method. Hazard ratios (HRs) were calculated via Cox proportional hazards regression models.Over the follow-up period of up to 9.17 years (with a median [IQR] time to death of 6.58 years), equivalent to 18731.56 [weighted 3.46*10 8 ] person-years, there were a total of 576 recorded deaths. Participants with CI exhibited a 1.96-fold higher risk of all-cause mortality (95% CI: 1.55-2.49; p < 0.01) and a 2.8-fold higher risk of CVD-specific mortality (95% CI: 1.83-4.29; p < 0.01) in comparison to participants without CI. Among participants with CI, concurrent hypertension comorbidity was linked to a 2.73-fold elevated risk of all-cause mortality (95% CI: 1.78-4.17; p < 0.01) and a 5.3-fold elevated risk of CVD-specific mortality (95% CI: 2.54-11.04; p < 0.01). Further stratified analyses revealed that the combined effects of hypertension and CI on all-cause and CVDspecific mortality were more pronounced in participants aged 60 to 69 years compared to those aged 70 to 80 years (p for interaction <0.01). The primary findings exhibited resilience across a series of sensitivity analyses.Conclusions: Participants with CI exhibited a markedly elevated risk of all-cause and CVD-specific mortality when coexisting with hypertension. Appropriate management of hypertension in patients with CI may be helpful in reducing the excess risk of death.